International Law Perspective of The State's Preventive Role in Responding to Climate Refugees - Rafika Rizky Aulia Rahman; Adam Muhammad Yanis (NEGREI: Academic Journal of Law and Governance, 2025)
Climate change is one of the primary issues widely discussed by the international community, particularly in relation to rising sea levels that threaten island nations. The submergence of state territories has become a major factor driving the emergence of climate refugees, who are forced to leave their home countries in search of shelter elsewhere. As coastal land becomes submerged and uninhabitable, populations are forced to relocate, giving rise to the phenomenon of climate refugees. However, current international legal frameworks do not explicitly recognize climate-induced displacement within the traditional refugee definition under the 1951 Refugee Convention and its 1967 Protocol. This research used the doctrinal method of legal research and is supported by secondary data based on available literature. This article examines the legal and geopolitical implications of disappearing state territory and explores the preventive role of states in responding to the emergence of climate refugees. Focusing on case studies such as Kiribati and Indonesia’s involvement through regional cooperation, the paper analyzes how states can enact proactive policies, from relocation strategies to transnational partnerships to mitigate future risks. Through doctrinal legal analysis, this study proposes state-centered strategies for strengthening global governance in addressing climate-induced migration. It further explores how states can anticipate and address the potential loss of national territory due to sea level rise in the future.